Learning environment and proactive personality : the mediating roles of motivational orientation - Hamimah binti Hashim (Kulliyyah of Education, International Islamic University Malaysia, 2018)
This study examined the hypothesized model which postulated the causal relationships between perceived learning environmental factors namely, lecturers, peers and physical learning environment; proactive personality; motivational orientation (controlled) and creativity index. The main objective of this study was to determine the role of motivational orientation as mediating variable by testing a hypothesized structural model. Using responses to a creativity test and items survey (n=374) among first degree graduating students in UiTM Shah Alam, the structural model was tested against the data for its fitness, via AMOS version 16.0. The result indicated that controlled motivational orientation was a significant mediator for the relationship between proactive personality and creativity index. The percentages of variance explained by these variables were 50 % (motivational orientation) and 87% (creativity index). The study also established the validity and reliability of the instruments and the hypothesized model. Additionally, the findings indicated that there were significant relationships between the variables measured at p <0.05. The findings supported the assumptions of Amabile's componential theory of creativity. In addition, it also highlighted the role of proactive personality as the factor that influenced the creativity index via controlled state of motivation. Finally, theoretical and practical implications were discussed in the context of learning environments and personality trait of the graduating students as the significant indicators for the creativity index.